Development of Activated Carbon Material from Oil Palm Empty Fruit Bunch for CO2 Adsorption - Irsandi Dwi Oka Kurniawan; Randy Yusuf Kurniawan; Nurul Widiastuti; Lukman Atmaja; Anis Shofiyani (Jurnal Teknik ITS, 2019)
This study aims to determine the CO2 adsorption capacity of activated carbon doped with nitrogen. Activated carbon is carbonized from oil palm empty fruit bunches (OPEFB). The results of lignocellulose analysis from OPEFB, 42.87 wt% of hemicellulose, 27.31 wt% of lignin, 23.02 wt% of cellulose and 6.80 wt% of ash. Potassium hydroxide is used as an activating agent and urea as a nitrogen precursor with an OPEFB mass: urea is 1: 1 to 1: 5. The method used is single-step, where carbonization-activation-doping is made into one process. Activated activated carbon is characterized by Fourier-Transform Infrared (FTIR), X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET) isotherm, and scanning electron microscope (SEM) with energy dispersive X-ray. Infrared spectra showed that N-doped activated carbon was successfully synthesized. Diffractogram shows an amorphous structure with graphitic plane (002) and (100). ACN11 produces the highest surface area of 1309.47 m2 g-1. The results of gravimetric CO2 adsorption at 30 °C and 1 atm conditions resulted in the largest CO2 adsorption capacity of ACN14 at 15.02 wt%. The ACN11 and ACN14 adsorption kinetics models followed the intraparticle diffusion model with R2 values of 0.95 and 0.97.